MODL-03. IDH-MUTANT GLIOMA GWAS ALLELE RS55705857 ON 8Q24 IS CHANGING THE DYNAMICS OF UNPATTERNED CEREBRAL ORGANOID DEVELOPMENT. (14th November 2022) - Drucker, Kristen; Kollmeyer, Thomas; Yanchus, Connor; De Lorenzo, Silvana; Eckel-Passow, Jeanette; Lachance, Daniel Honore; Schramek, Daniel; Jenkins, Robert
Abstract: BACKGROUND: The topologically associated domain (TAD) on 8q24 surrounding MYC is important for many types of cancer. The region is also important in the formation of IDH-mutant glioma; the risk allele rs55705857 being associated with the development of these tumors. The rs55705857 risk allele significantly increased the formation of tumors in an IDH-mutant mouse model. Cerebral organoids have been found to recapitulate the early development of the brain. We hypothesized that the rs55705857 risk allele may alter the phenotype of cerebral organoids. METHODS: Isogenic induced pluripotent stem cells (iPSCs) were developed with (n=3) and without (n=2) the rs55705857 risk allele from the parental cell line PGP-1 (GM23338). These cells were cultured and differentiated into unpatterned cerebral organoids and observed throughout differentiation. Organoids were fixed, sectioned, and stained by H&E and immunofluorescence. RESULTS: Organoids containing the risk allele were smaller throughout development, starting at the embryoid body stage and continuing up to over 75 days in culture, compared to two isogenic non-risk lines. At 4 weeks the risk allele containing organoids also contained a larger number of small rosette-like neuroepithelia, instead of the more continuous neuroepithelia observed in the non-risk allele organoids. At 75 days, the organoids with the risk allele maintained a larger proportion of Sox2 positive cells, which are enriched in the tight clusters of small cells with round nuclei. CONCLUSIONS: The risk allele rs55705857 in the MYC TAD at 8q24 is altering the development of unpatterned cerebral organoids. This difference is visible as early as embryoid body development and persists through neuroepithelial development. Further studies of these differences may help our understanding of how rs55705857 accelerates IDH-mutant glioma development.